2003
DOI: 10.1021/ef0300747
|View full text |Cite
|
Sign up to set email alerts
|

Class- and Structure-Specific Separation, Analysis, and Identification Techniques for the Characterization of the Sulfur Components of JP-8 Aviation Fuel

Abstract: Methods have been described for separating the sulfur content of aviation fuels into chemical classes for identification and quantitation. These separation methods simplified the fuel matrix, which allowed non-element-specific detection methods, such as mass spectrometry (MS), to be used for sulfur detection. These matrix simplification methods also enhanced the ability of element-specific detection methods, such as atomic emission detection (AED), to identify sulfur species that are present in the fuel. Separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…Sulfur compounds in aviation fuels were found to occur mainly as thiols, sulfides, and disulfides while thiophenes and DBTs are minor constituents (Link et al, 2003). Somewhat similar classes of sulfur components in a fluid catalytic cracking (FCC) gasoline were thiols, sulfides, thiophene and alkylthiophenes, tetrahydrothiophene, thiophenols, and benzothiophene (Hatanaka et al, 1997;Cheng et al, 1998).…”
Section: Sulfur Compounds In Crude Oil and Petroleum Productsmentioning
confidence: 99%
“…Sulfur compounds in aviation fuels were found to occur mainly as thiols, sulfides, and disulfides while thiophenes and DBTs are minor constituents (Link et al, 2003). Somewhat similar classes of sulfur components in a fluid catalytic cracking (FCC) gasoline were thiols, sulfides, thiophene and alkylthiophenes, tetrahydrothiophene, thiophenols, and benzothiophene (Hatanaka et al, 1997;Cheng et al, 1998).…”
Section: Sulfur Compounds In Crude Oil and Petroleum Productsmentioning
confidence: 99%
“…To improve the economics of ODS, we therefore set out to understand the role of the activated carbon promoter so as to reduce its use, thereby improving process economics. In a second published work [19] we showed that, depending on the types of sulfur compounds present in the fuel, either oxidization of the benzothiophene (BT) content [62] or removal of oxidized sulfides/disul fides/thiophenes [63] could limit overall ODS performance. Given that BT oxidation can limit ODS performance, the motivation of our ongoing research was the selection of the best carbon material for oxidation of BT compounds [19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the above considerations, determination of OSCs in aqueous environmental samples is necessary and provides useful information about the source of input and quality of water. The determination of OSCs in aqueous environmental samples is usually carried out by methods including gas chromatography (GC) [8,9], gas chromatography-mass spectrometry (GC-MS) [10,11] and liquid chromatography [12].…”
Section: Introductionmentioning
confidence: 99%